Shock Cryptic, emerging diagnostic: Shock críptico, diagnóstico incipiente - Ayala García, Ricardo J. (2021)
Cryptic shock is a poorly identified clinical entity, and it still describes a patient with signs of tissue hypoperfusion without affecting blood pressure. In the emergency department, it is important to identify signs of hypoperfusion and evaluate various hidden sources of infection by taking a complete medical history, a thorough physical examination, and, if necessary advanced imaging. It is necessary to conclude that the importance of the timely diagnosis of this clinical entity helps to improve the prognosis significantly.